2010
DOI: 10.1073/pnas.1015652107
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness of the first order in blindsight

Abstract: At suprathreshold levels, detection and awareness of visual stimuli are typically synonymous in nonclinical populations. But following postgeniculate lesions, some patients may perform above chance in forced-choice detection paradigms, while reporting not to see the visual events presented within their blind field. This phenomenon, termed "blindsight," is intriguing because it demonstrates a dissociation between detection and perception. It is possible, however, for a blindsight patient to have some "feeling" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 31 publications
3
33
0
1
Order By: Relevance
“…The latter refers to well-documented observations that blind subjects with severely damaged primary visual cortex can still perceive unseen stimuli involving higher cortical functions. 41 …”
Section: Discussionmentioning
confidence: 99%
“…The latter refers to well-documented observations that blind subjects with severely damaged primary visual cortex can still perceive unseen stimuli involving higher cortical functions. 41 …”
Section: Discussionmentioning
confidence: 99%
“…The low spatial frequency cut-off was 2 cycles per degree (for the exact method of filtering and normalizing images refer to Bannerman et al, 2012). We decided to include the 2 c/° cut-off because the remaining information was in the range of the optimal frequencies for detection and awareness in blindsight reported by Sahraie et al (2010Sahraie et al ( , 2013) and comparable to the parameters applied in previous studies by Vuilleumier, Armony, Driver and Dolan (2003) and Bannerman et al (2012). Previous work also indicated that participants were able to correctly classify the emotion expression at this low spatial frequency range (Bannerman et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…There does seem to be converging evidence that, at least following injury to the developed adult brain, damage to V1 can eliminate the capacity to process information that might be necessary for making discriminations about contour, colour, texture, and figure-ground contrasts (Alexander & Cowey, 2010;Alexander & Cowey, 2013;Kentridge, Heywood, & Weiskrantz, 2007;Pavan, Alexander, Campana, & Cowey, 2011;Sahraie et al, 2010). If this is the case, then it is a very interesting topic for research that could lead to important insights about the phenomenon and the residual processing that subserves blindsight subjects' capacities.…”
Section: Resultsmentioning
confidence: 92%
“…Sahraie, Hibbard, Trevethan, Ritchie, and Weiskrantz (2010) have shown that DB's reported awareness depends on first-order (luminance defined) stimuli, despite the fact that he can perform above chance with second-order (contrast defined) stimuli in a forced-choice discrimination task (see Fig. 2).…”
Section: Type-2 Blindsight As a Form Of Cognitive Awarenessmentioning
confidence: 90%
See 1 more Smart Citation